Kemahiran pengurusan stres dalam kecerdasan emosi dan hubungannya dengan kepuasan hidup remaja - Abdul Adib Asnawi,; Lailawati Madlan @ Endalan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Adolescent stages are challenging and stressful. Stress management skills for this group are important to achieve a high quality life satisfaction. The main objective of this study was to evaluate the association between stress management skills and life satisfaction among secondary school students. In addition, this study also examined the differences in stress management skills and life satisfaction by gender. This survey study involved 1,067 respondents consisting of students from form one to six (aged 13 to 18 years old) around Kota Kinabalu and Kudat, Sabah. The research instruments used in this study were the Emotional Quotient Inventory Youth Version (EQ-i: YV) and Cantril's Vertical VisualAnalog Scale Ladder of Life Satisfaction which were translated into Malay. Data were analyzed using correlation test and independent sample t-test. Results showed that there was a positive correlation between stress management skills and life satisfaction among secondary school students. Meanwhile, the results of the independent sample t-test analysis showed that there were differences in stress management and life satisfaction by gender. Results highlight that stress management skills are very important because it is directly related to life satisfaction, especially for adolescents or generation Z.